Engineering of surface properties of Ni-CeZrAl catalysts for dry reforming of methane. (15th January 2022) - Wen, Junjie; Xie, Yu; Ma, Yanping; Sun, Haiyang; Wang, Huimin; Liu, Mo; Zhang, Qiulin; Chen, Jianjun
Graphical abstract: Highlights: Ni-CeZrAl with unique surface properties presented superior catalytic performance in DRM. The superior catalytic activity was due to rich oxygen vacancies and active oxygen species. The optimum active site-support interaction resulted in the high dispersion of Ni active sites. Abstract: Ni-CeZrAl catalyst prepared by a facile co-precipitation method was applied for dry reforming of methane (DRM). DRM catalytic performance of Ni-CeZrAl presented the highest methane conversion of 38.1% at 650 °C, and remained stable at 700 °C for 50 h without deactivation. Kinetic investigations further showed the lowest apparent activation energy (34.5 kJ/mol) of DRM reaction and the highest CH4 TOF value (7.62 × 10 −2 s −1 ) at 640 °C over Ni-CeZrAl. The surface properties of these samples were systematically characterized by H2 -chemisorption, H2 -TPR, XPS, Raman, CO2 -TPD and O2 -TPD. It can be found that the superior catalytic behaviors of Ni-CeZrAl catalyst were closely associated with its high dispersion of surface Ni 0 active phase. More importantly, ample oxygen vacancies and basic sites favored the formation of disordered carbon and effectively protected the Ni active sites. The inferior activity in Ni-CeAl was due to the formation of NiAl2 O4 inactive spinel phase. Similarly, weak interaction and fewer active sites resulted in the inferior catalytic performance of Ni-CeZr. Hence, unique surface properties of Ni-CeZrAl with the optimum active site-support interaction were responsible for considerable performance. This work provides a guidance to design high performance Ni-based catalysts for DRM.